Careful Cracks: Resistant Practices of Care and Affect-ability - Ludovica D'Alessandro (Krisis, 2022)
Throughout the COVID-19 pandemic, several institutional policies and discourses, speaking in tandem with a ‘health’ and ‘financial crisis’, have highlighted what seems to be the consequences of an aporetic disentanglement of capitalist relations of production and reproduction. Indeed, partial halts to economic production in the wake of COVID-19 have become equivalent – through symbolic and material actualisations of vulnerability and care – to a suspension of people’s capacity to sustain themselves. This dynamic has thus overshadowed alternatives to the capitalist tie of economic production with social reproduction. Resisting this landscape, local solidarity groups have emerged globally to counter the flattening of reproduction for the perpetuation of the socio-economic status quo by creating networks of mutual aid and support. Learning from these movements, I propose affect-ability as a philosophically productive term and tool to conceptualise resistant practices of care, toward underscoring the inherent relationality and vulnerability of bodies as well as its unequal and inequitable effects, while rethinking the notion of care itself from these ontological, political, and ethical premises.